2000
DOI: 10.1111/j.1745-9125.2000.tb00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Sanction Threats, Gender, and Crime: A Test and Elaboration of Power‐control Theory*

Abstract: This research addresses the need to incorporate the perceived threats of informal sanctions, specifically, shame and embarrassment, into the power‐control model. First, the possibility that gender differences exist in the perceived threats of shame and embarrassment, as well as legal sanctions, and that these differences vary between more patriarchal and less patriarachal households of origin is explored. Second, the relative impact of the informal sanction threat variables compared with the formal legal sanct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 76 publications
2
56
1
Order By: Relevance
“…This was consistent with much prior deterrence-related research indicating that informal, and self-imposed sanctions tended to overpower formal sanctions (Blackwell, 2000). Including shame and embarrassment also rendered the effect of low self-control insignificant among females in more patriarchal households, a significant attenuation (z m = 3.323).…”
Section: Replacing Risk With Legal Sanctions Shame and Embarrassmentsupporting
confidence: 88%
See 2 more Smart Citations
“…This was consistent with much prior deterrence-related research indicating that informal, and self-imposed sanctions tended to overpower formal sanctions (Blackwell, 2000). Including shame and embarrassment also rendered the effect of low self-control insignificant among females in more patriarchal households, a significant attenuation (z m = 3.323).…”
Section: Replacing Risk With Legal Sanctions Shame and Embarrassmentsupporting
confidence: 88%
“…In other words, mothers' supervision and girls' affection for mothers impacted girls' risk preferences, risk perceptions, and delinquency while fathers were more likely to impact their sons' attitudes and behaviors. Ultimately, Blackwell (2000) concluded that this was not necessarily out of line with power-control theory, drawing attention to the potential that fathers' greater involvement in child-rearing in less patriarchal households might be decreasing boys' delinquency.…”
Section: Enter Power-control Theorymentioning
confidence: 89%
See 1 more Smart Citation
“…Baer [81] found that a mother's direct monitoring of her children's activities is a significant deterrent of delinquent offending across all three racial-groups in the study's sample but a father's direct supervision is a significant deterrent for European-American (i.e., white) but not African-American (i.e., black) or Mexican-American (i.e., Hispanic) children. There could also be differences in terms of perceived threats of informal sanctions, such as shame and embarrassment, which can produce gender differences in offending and these differences can vary by type of household [82]. Females are more likely to be strongly attached to parents and feel more shame than males [83].…”
Section: The Role Of Gender and Place On Parental Social Controlmentioning
confidence: 99%
“…Some studies led us to expect low violence rates for Muslim Thai girls, especially in public places: Sherer and Sherer (2008) argued that Arab girls in Israel, who grew up in a traditional society, and who had less freedom than Western girls, were less likely to be involved in violent encounters. Blackwell (2000) found varying effects of threats of informal sanctions, specifically shame and embarrassment, on males and females, depending on the extent of patriarchy in their households of origin. Although Thailand is also a patriarchal society, and probably shares the tendencies of traditional societies, we found the southern Thai girls had higher mean scores of violence than the girls in the other two provinces.…”
Section: Differences Among Provincesmentioning
confidence: 97%